Povoamento e organização do território do Baixo Douro na época da monarquia asturianana - Lima, António Manuel de Carvalho (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
After a short description of physical landscapes of lower Douro valley and its main routes, the settlement pattern and organization at the time of the Asturian kingdom is analyzed, taking out on both documentary and material sources. Having seen how the land taking and the settlement pattern based on the civitates served to the purposes of the Asturian monarchy to incorporate the Douro valley under its ruling sphere, we try to skim over the socio-economic and politic-military changes brought to light from the end of the first millennium AD. These changes would drive the territorial organization into another settlement pattern.